2017
DOI: 10.1007/s11248-017-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recombinase activity of Cre–ERT2 in vivo

Abstract: Inducible Cre-ERT recombinase technology is widely used for gene targeting studies. The second generation of inducible Cre-ERT recombinase, hemizygous B6.129S-Tg(UBC-cre/ERT2)1Ejb/J (hereafter abbreviated as Cre-ERT2), a fusion of a mutated estrogen receptor and Cre recombinase, was engineered to be more efficient and specific than the original Cre-ERT. The putative mechanism of selective Cre-mediated recombination is Cre sequestration in the cytoplasm in the basal state with translocation to the nucleus only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 13 publications
4
52
0
Order By: Relevance
“…Indeed, a similar recent study provided similar conclusions [22]. Furthermore, CreER leakiness has previously been observed in both fluorescent reporter and conditional knock‐out studies [23,24], suggesting that this is highly likely a conserved limitation of the CreER system. The authors also exclude that the tamoxifen‐independent recombination was associated to the strong synthetic ‘CAG’ promoter present in some reporter strains.…”
Section: Figuresupporting
confidence: 75%
“…Indeed, a similar recent study provided similar conclusions [22]. Furthermore, CreER leakiness has previously been observed in both fluorescent reporter and conditional knock‐out studies [23,24], suggesting that this is highly likely a conserved limitation of the CreER system. The authors also exclude that the tamoxifen‐independent recombination was associated to the strong synthetic ‘CAG’ promoter present in some reporter strains.…”
Section: Figuresupporting
confidence: 75%
“…Several dopaminergic neuron-specific Cre recombinase expressing mouse lines (DAT-Cre) have also been created (Backman et al, 2006;Ekstrand et al, 2007;Turiault et al, 2007;Zhuang, Masson, Gingrich, Rayport, & Hen, 2005). Despite concerns about specificity of Cre expression (Papathanou, Dumas, Pettersson, Olson, & Wallen-Mackenzie, 2019) and spontaneous tamoxifen-independent recombination ("leakiness") of CreERT2 (Kristianto, Johnson, Zastrow, Radcliff, & Blank, 2017;Sandlesh, Juang, Safina, Higgins, & Gurova, 2018), these mouse lines have been extremely useful to study functions of multiple genes in dopaminergic neurons. For example, analysis of sonic hedgehog (Shh)/DAT-Cre mice revealed that Shh expression in dopaminergic neurons is essential for their maintenance in the adult animals, as the mutant mice exhibited neurodegeneration, locomotor, and gait abnormalities (Gonzalez-Reyes et al, 2012).…”
Section: Etiological Modelsmentioning
confidence: 99%
“…Many marker genes specific for adult astrocytes are also expressed in NPCs during development (Ferenczy et al, 2013;Foo and Dougherty, 2013), many of which become neurons. This necessitates the employment of inducible strategies, such as CreERT2, although they can be inefficient or hard to tune (Chow et al, 2008;Kristianto et al, 2017). The Slc1a3 gene was used previously to drive Cre using a BAC method whereby a large region of genomic DNA encompassing an entire gene is modified to carry coding sequence for Cre and then returned to the genome where it lands in a random location.…”
Section: Precise Targeting Of Astroglia Is Challengingmentioning
confidence: 99%